2008
DOI: 10.1051/parasite/2008153389
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunity inToxoplasma gondiiinfection

Abstract: Summary :Toxoplasma gondii is an intracellular parasite that frequently infects a large spectrum of warm-blooded animals. This parasite induces abortion and establishes both chronic and silent infections, particularly in the brain. Parasite penetration into the host activates a strong anti-parasite immune response. In the present paper, we will discuss the interplay between innate and adaptive immunity that occurs within the infected intestine to clear the parasite and to maintain intestinal homeostasis despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Our dose-dependence analyses indicated that 30 μg of rTgPDI evoked a significant Th1-type immune response, as demonstrated by high levels of IFN-γ, IL-2 and IgG2a ( P <0.01), while no obvious changes in IL-10 of Th2-type immune response. In addition to cellular immune responses, both humoral immunity, associated with increased total IgG antibody levels, and mucosal immune responses, resulting in IgA production, are important in controlling T. gondii infection [43], [44]. Our results showed that the administration of 30 μg of rTgPDI resulted in higher levels of IgG and IgA in sera compared with the other treatments.…”
Section: Discussionmentioning
confidence: 62%
“…Our dose-dependence analyses indicated that 30 μg of rTgPDI evoked a significant Th1-type immune response, as demonstrated by high levels of IFN-γ, IL-2 and IgG2a ( P <0.01), while no obvious changes in IL-10 of Th2-type immune response. In addition to cellular immune responses, both humoral immunity, associated with increased total IgG antibody levels, and mucosal immune responses, resulting in IgA production, are important in controlling T. gondii infection [43], [44]. Our results showed that the administration of 30 μg of rTgPDI resulted in higher levels of IgG and IgA in sera compared with the other treatments.…”
Section: Discussionmentioning
confidence: 62%
“…Intranasally administered rTgADF was able to penetrate the nasal epithelium, where it was processed by the antigen-presenting cells. This process leads to the activation of T and B cells that develop into IgA plasma cells [ 17 , 25 , 26 ]. Mature sIgAs are compounded in the regional lymph nodes, and then enters circulation via the thoracic duct.…”
Section: Discussionmentioning
confidence: 99%
“…It is also capable of causing abortion or birth defects during congenital infection ( 75 , 76 ). Toxoplasma transmission occurs by oral ingestion of infectious tissue cysts or oocysts; hence, intestinal mucosal immunity constitutes the first line of defense and is one of the most important barriers against T. gondii ( 13 , 77 , 78 ). In the small intestine, T. gondii differentiates into tachyzoites, the rapidly replicating form of the parasite, which ultimately disseminates infection beyond the intestinal mucosa, colonizing other tissues, such as skeletal muscle and the central nervous system, before it differentiates into the bradyzoite form, which establishes latent infection in the form of tissue cysts ( 13 ).…”
Section: Intestinal Mucosal Immunity To Pathogenic Protozoamentioning
confidence: 99%